Small Cell Carcinoma of Urinary Bladder: Analysis from a Tertiary Cancer Care Center of India - Ram, Dharma; Rajappa, Suhas Kodasoge; Babu Koyyala, Venkata Pradeep; Chatterjee, Smaranjeet; Bhakuni, Yogendra Singh; Shukla Singh, Himanshu Amitabh; Singh, Amitabh; Rawal, Sudhir (Indian Journal of Medical and Paediatric Oncology, 2018)
Context: Small cell cancer of the urinary bladder. Aims: Small cell carcinoma of the bladder is a rare histological subtype, which is particularly aggressive and global literature available describing this entity is sparse. This review of our database was to evaluate clinicopathological and survival outcomes of these patients. Subjects and Methods: The present study was a retrospective analysis of patients with small cell bladder cancer for past 6 years at Rajiv Gandhi Cancer Institute and Research Center, New Delhi. Results:: Most of the patients in our study presented with limited stage disease. The overall survival and disease-free survival (DFS) was 49% and 51.07% at 2 years, respectively. Preoperative chemotherapy with surgical resection has shown significant survival and DFS benefit. Stage at presentation also affected the survival and DFS though it did not reach statistical significance. Conclusions: Small cell bladder cancer is a rare disease with dismal prognosis. Multimodality treatment with neoadjuvant chemotherapy should be the preferred treatment for limited stage disease.
Keywords: India; neuroendocrine carcinoma; small cell bladder carcinoma